Geometry Formation and Software Realization of Straight Profile Hourglass Worm - Shoubang Zheng; Shuncheng Yang; Lixuan Zhou; Yongqin Qiao; Weiping Fu (Jixie chuandong)
Considering the status quo of processing，to avoid conventional spatial meshing theory，and relying on actual production projects，the forming principle of straight profile hourglass worm is analyzed in terms of geometry. After processing verification，it meets the design and use requirements. Combining with examples，presents readers with a software implementation method for reprinting.